2013
DOI: 10.1002/dev.21149
|View full text |Cite
|
Sign up to set email alerts
|

Salivary cytokines in healthy adolescent girls: Intercorrelations, stability, and associations with serum cytokines, age, and pubertal stage

Abstract: Theoretically, the measurement of cytokines in saliva may have utility for studies of brain, behavior, and immunity in youth. Cytokines in saliva and serum were analyzed across three annual assessments in healthy adolescent girls (N = 114, 11-17 years at enrollment). Samples were assayed for GM-CSF, IFNγ, IL-1β, IL-2, IL-6, IL-8, IL-10, IL-12p70, TNFα, adiponectin, and cotinine. Results revealed: (1) cytokine levels, except IFNγ and IL-10, were detectable in saliva, and salivary levels, except IL-8 and IL-1β, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 91 publications
(79 reference statements)
7
66
2
2
Order By: Relevance
“…We found strong positive associations between salivary adiponectin and indices of oral inflammatory activity and oral health (IL-1β, IL-6, IL-8, TNFα and MMP-8). While consistent with findings from a previous study of healthy adolescent girls (Riis et al, 2013), these findings are contrary to findings from in vitro studies of adiponectin's effect on oral epithelial cells, primary gingival fibroblasts, and periodontal ligament cells (Iwayama et al, 2012;Kraus et al, 2012). Together, the findings demonstrate the importance of assessing adiponectin's relations with inflammation and health using various approaches and populations; the function and proprieties of adiponectin may vary based on characteristics of the hormone, its receptors and the health of the individual (Almabouada et al, 2013;Li & Wu, 2012).…”
Section: Adiponectin and Inflammatory Activity And Oral Healthsupporting
confidence: 92%
See 2 more Smart Citations
“…We found strong positive associations between salivary adiponectin and indices of oral inflammatory activity and oral health (IL-1β, IL-6, IL-8, TNFα and MMP-8). While consistent with findings from a previous study of healthy adolescent girls (Riis et al, 2013), these findings are contrary to findings from in vitro studies of adiponectin's effect on oral epithelial cells, primary gingival fibroblasts, and periodontal ligament cells (Iwayama et al, 2012;Kraus et al, 2012). Together, the findings demonstrate the importance of assessing adiponectin's relations with inflammation and health using various approaches and populations; the function and proprieties of adiponectin may vary based on characteristics of the hormone, its receptors and the health of the individual (Almabouada et al, 2013;Li & Wu, 2012).…”
Section: Adiponectin and Inflammatory Activity And Oral Healthsupporting
confidence: 92%
“…Furthermore, based on previous studies (Riis et al, 2013), we hypothesize that salivary adiponectin is positively associated with measures of oral inflammatory activity and oral health, and, therefore, we also examine the serum-saliva correlation for adiponectin when controlling for measures of oral inflammatory activity and oral health. We hypothesize that the serum-saliva correlation will become stronger when we control for indicators of oral inflammation and oral health.…”
Section: Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…With IL-6 as the only biomarker measured, Grisius et al [34] and Minetto et al [35] found no significant inter-compartmental correlation in healthy North American and Italian adults, respectively; this was also the experience of Fernandez-Botrán et al [36], investigating emotionally-abused women, again with IL-6 as their only cytokine biomarker of interest. Among 8 cytokines, including the same 5 assayed in the present study, measured concurrently in plasma and saliva in healthy female adolescents, Riis et al [37] found only IL-1B to reach a statistically-significant correlation between compartments. In 2013, Byrne et al [38] evaluated 11 cytokines, including 4 of the 5 cytokines measured here, across the anatomical compartments in healthy Australian adolescents; they found significant associations only for IL-2, IL-12 and INF-γ, but for none of the cytokines measured in the present study.…”
Section: Discussionmentioning
confidence: 51%
“…It is true that salivary IL-1b only showed an indirect association with plasma levels (Riis et al, 2014). However, our new results show saliva an independent tool to investigate markers of the performance outcome.…”
mentioning
confidence: 62%